Surface Energy - Aliofkhazraei, Mahmood (IntechOpen, 2015)
The words hydro, phobic and philic are derived from Greek and they mean water, fear and adoration respectively. These words are being used to define the interaction of water and other materials. As an example, these words are being used in classification of liquids and solids based on their solubility in water, as well as classification of solid surfaces regarding to their wettability. A lot of surfaces in the nature have Superhydrophobic and self-cleaning properties. For example the wings of a butterfly, leaves of some plants, including cabbage and Indian Cress, have the mentioned properties. The best example is the LOTUS leaf. This book collects new developments in the science of surface energy.